An exploratory survey of public health nurses’ knowledge, skills, attitudes, and application of the Quad Council Competencies - Harmon, Monica; Joyce, Barbara L.; Johnson, Regina (Gina) H.; Hicks, Vicki; Brown‐Schott, Nancy; Pilling, Lucille; Collinge, Rachelle; Brownrigg, Vicki (Public health Nursing, 2020)
Objective A collaborative research team of community/public health nursing faculty and public health nurses surveyed public health nurses to explore knowledge, skills, attitudes, and application of the Quad Council Competencies for Public Health Nurses (QCC‐PHN). Methods Evaluate the knowledge, skills, attitudes, and application of the 2011 QCC‐PHN by public health nurses. Design A descriptive, cross‐sectional design was used to answer the hypothesis related to the study objective. A convenience sample of 308 public health nurses completed an online survey. Measurements ANOVA was used to determine the difference between the knowledge, skills, attitudes, and application of community/public health nurses (C/PHNs) regarding the QCC‐PHN based on nursing specialty preparation, years of nursing experience, and years of C/PHN experience. Results C/PHNs are described and differences in knowledge, skills, attitudes, and application are delineated. A statistically significant difference was found in knowledge and attitude based upon years of C/PHN experience. Conclusions Recommendations are proposed for increasing the QCC‐PHN awareness, implementation, and evaluation to effectively enhance the practice of nursing C/PHN.